Pension Reforms; Effects on Intergenerational Risk-Sharing and Redistribution - Agneta Kruse (Lund University, School of Economics and Management, Department of Economics, 2000)
Projections show public pensions to take an increasing share of GDP. This has lead to increased activity in the reform area and resulted in a plethora of reforms ranging from marginal to more radical ones. The former kind has often tried to hold back increasing expenditure by decreasing benefit levels, increasing statutory retirement age etc., while the latter may be exemplified by the Italian or Swedish reforms. The marginal reforms implemented give an impression of being rather haphazard. Accelerating expenditures seem to justify all forms of reduction; if the indexing has been by wages, then the change is to price indexing, and vice versa. In this paper the analysis of reforms will concentrate on the different kinds of risks or threats a pension system is exposed to, notably economic, demographic and political risks and how these risks change with differently designed reforms. The paper will also treat distribution effects of different designs and of the risk exposure. What does the experience of 30 - 40 years of public pension systems tell us about the effects of different designs? Are there any recommendations to be drawn from economic theory?
Keywords: H55; J14; J26; 330; Social insurance; pensions; intergenerational risk-sharing